Checklist of Nematoda associated with the fishes of Brazil - Luque, José L.; Aguiar, Julio C.; Vieira, Fabiano M.; Gibson, David I.; Santos, Cláudia Portes (Zootaxa, 2011)
Seventy-four genera comprising approximately 140 named and 75 undetermined species of adult and larval nematodes are associated with about 330 named and 50 undetermined species of marine, brackish and freshwater fishes from Brazilian waters. These are listed with information on their hosts, habitat, distribution and records. A key to these parasites at the generic level is provided.